Evidence of Psychological Manipulation in the Process of Violent Radicalization: An Investigation of the 17-A Cell - González, Irene; Moyano, Manuel; Lobato, Roberto M.; Trujillo, Humberto M. (Frontiers in Psychiatry, 2022)
The violent radicalization of individuals and groups affects the safety, coexistence, and social cohesion of communities around the world. In Europe, an increase of radicalization has been reported, and recruiters play an important role in violent mobilization by galvanizing young recruits through psychological manipulation. This study examines the violent behavior of nine young boys, aged 17-28 who were supposedly recruited by an imam to carry out the terrorist attacks in Barcelona and Cambrils on August 17, 2017, which killed 16 people and injured more than 150. The objectives of this investigation are: a) to determine the influence of the social context and group dynamics in the process of radicalization of young people, and b) to detect indicators of psychological manipulation in the core of the evaluated group. We hypothesized that the use of psychological manipulation techniques by recruiters 1) facilitates the recruitment of young people towards radical groups, 2) legitimizes the ideological motivation for violence, and 3) consolidates the bonds between members of the group. We tested our hypotheses through deductive content analysis. Using this approach, we gathered and analyzed the judicial order of the National High Court related to “Operation Ramblas” and the police proceedings of El Cuerpo de Mossos d’Esquadra (CME) regarding the Barcelona and Cambrils attacks on August 17, 2017. An observation record sheet with different indicators of psychological manipulation was coded by two independent experts to reveal the most frequent psychological manipulation techniques. Our results indicate that recruiters often use psychological manipulation techniques to radicalize individuals. The most frequently used techniques were control of attention, control of information, denigration of critical thinking, identification with the group, and authoritarian leadership. These techniques were used by the recruiter to legitimize the use of violence. Similarly, recruiters were also actively involved in strengthening the radical network by providing meaning to its members through violence-justifying narratives. This research shows that recruiters use psychological manipulation techniques to recruit and mobilize young people into violent extremism. We highlight the need for prevention and psychosocial interventions to steer youth away from violent extremism, offering alternatives to violence.